Remittances and Inflation in Egypt: An Econometric Study Using an ARDL Model - Youssef, Waleed Mohamed (The Arab Journal of Administration, 2024)
This paper analyzes the impact of remittance inflows on inflation in Egypt. It uses an Autoregressive Distributed Lag (ARDL) model to identify the short-run and long-run sources of inflation in Egypt during 1975-2019, while including remittance inflows among the inflation determinants. The results show that remittance inflows to Egypt have inflationary pressures in the long run, whereas such inflationary pressures are not confirmed in the short run. Other sources of inflation in the long run include the output gap, money supply, and openness. The results indicate the exchange-rate pass through effect is transitory, since it exists only in the short run.